Strict compliance with ESC therapeutic guidelines after myocardial infarction treated with invasive strategy correlates with improved 18-month outcomes. (25th November 2020) - Kasprzak, J.D; Jankowski, E; Peruga, J.Z; Plewka, M; Krecki, R; Wcislo, T; Fiutowski, M; Jankowski, E; Hudzik, B; Gasior, M; Gierlotka, M
Abstract: Background: Despite improved early outcomes in patients (pts) with acute myocardial infarction (MI) in Poland with prevalent strategy of primary angioplasty by radial access, mid- and long-term outcomes are unsatisfactory. Objective: We hypothesized that strict implementation of secondary prevention ESC guidelines in post-infarction management may be related with improved mid-term clinical outcomes Methods: We compared 18-month outcomes of pts treated for MI with primary invasive strategy in a tertiary university hospital (NSTEMI 470/47%, or STEMI 535/53%; N=1005; Gr-L) with similar subset from national databases AMI-PL and PL-ACS (N=117307; NSTEMI 50966/43%, STEMI 64078/57%; Gr-Pol). Females represented 38.5% / 35.7% of Gr-L/Gr-Pol and mean age was 66.1±11.5 vs 65.8±11.9% (NS). The center implemented a strict policy of optimization prognosis-modifying prescriptions at discharge according to ESC guidelines. Endpoints over 18-month follow-up were defined as total mortality and combined clinical endpoint (death, stroke, recurrent MI, recurrent revascularization). Results: 30-days survival was comparable between Gr-L and national cohort. Key medicationrates were significantly higher for Gr-L vs most recent national estimates: renin-angiotensin blockers: 94% vs 79%, statins: 98% vs 75%, beta-blockers 95% vs 85%; ASA: 99% vs 94.5%, P2Y12 inhibitors 100% vs 83%. Rehabilitation was completed in 32% and 51% (after NSTEMI/STEMI) with national average around 20% - all differences p<0.05. Long-term mortality rate (overall 10.6% vs 14.5%, p=0.0005) and composite outcome rate was significantly improved in Gr-L – details shown in the table. Conclusions: Outcomes of MI patients in primary PCI era are related to optimized medical therapy and rehabilitation planned at discharge. Our study does not prove causality but indicates on strong association of strict compliance with ESC guidelines and improved 18-month outcomes including overall survival. Funding Acknowledgement: Type of funding source: None